2017
DOI: 10.1186/s41043-017-0079-z
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell disease and pregnancy outcomes: a study of the community-based hospital in a tribal block of Gujarat, India

Abstract: BackgroundSickle cell disease (SCD) is a hereditary blood disorder prevalent in tribal regions of India. SCD can increase complications during pregnancy and in turn negatively influence pregnancy outcomes. This study reports the analysis of tribal maternal admissions in the community-based hospital of SEWA Rural (Kasturba Maternity Hospital) in Jhagadia block, Gujarat. The objective of the study is to compare the pregnancy outcomes among SCD, sickle cell trait and non-SCD admissions. This study also estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
33
3
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 27 publications
3
33
3
9
Order By: Relevance
“…We had 56.94% babies less than 2.5 kg at birth similar to the higher rates observed earlier. 11,16,17,[20][21][22]24 Low Apgar score of 11% by Silva-Pinto et al and 34.5% by Muganyizi et al has been reported in babies born to SCD mothers, while we had 14.49% babies with low Apgar. 16,24 Because of prematurity, low birth weight and perinatal asphyxia due to IUGR, there was a high rate of neonatal ICU admissions.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…We had 56.94% babies less than 2.5 kg at birth similar to the higher rates observed earlier. 11,16,17,[20][21][22]24 Low Apgar score of 11% by Silva-Pinto et al and 34.5% by Muganyizi et al has been reported in babies born to SCD mothers, while we had 14.49% babies with low Apgar. 16,24 Because of prematurity, low birth weight and perinatal asphyxia due to IUGR, there was a high rate of neonatal ICU admissions.…”
Section: Discussionmentioning
confidence: 60%
“…17 This study also showed a higher incidence of eclampsia in consistent with an earlier metaanalysis and also reports from other states of India. 9,11,20 Intrauterine growth restriction was seen in more than onethird of the SCD women and such a higher incidence was shown in literature. 17,18,21 Chronic maternal anemia and hypertension in pregnancy resulting in reduced placental perfusion is the most likely reason for intrauterine growth restriction.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…2 Many studies have shown that pregnancy in sickle cell anaemia is associated with increased risk of maternal and foetal morbidity and mortality. 3,4,5,6 There is little data on the maternal, foetal and perinatal outcomes of women with sickle cell anaemia in India. No such studies were conducted in Kerala.…”
mentioning
confidence: 99%